Resolving the term “offshore aquaculture” by decoupling “exposed” and “distance from the coast” - Buck, Bela H.; Bjelland, Hans V.; Bockus, Abigail; Chambers, Michael; Costa-Pierce, Barry Antonio; Dewhurst, Tobias; Ferreira, Joao G.; Føre, Heidi Moe; Fredriksson, David W.; Goseberg, Nils; Holmyard, John; Isbert, Wolf; et al. (Frontiers in Aquaculture, 2024)
The terms “offshore” and “open ocean” have been used to describe aquaculture sites that are further from the coast or in higher energy environments. Neither term has been clearly defined in the scientific literature nor in a legal context, and the terms are often used interchangeably. These and other related terms (for example “exposed”, “high-energy”) variously refer to aspects of a site such as the geographic distance from shore or infrastructure, the level of exposure to large waves and strong currents, the geographic fetch, the water depth, or some combination of these parameters. The ICES Working Group (ICES, 2024) on Open Ocean Aquaculture (WGOOA) therefore identified a need to define the terminology to reduce ambiguity for these types of aquaculture sites or more precisely, to: (1) promote a common understanding and avoid misuse for different classifications; (2) enable regulators to identify the characteristics of a marine site; (3) allow farmers to be able to assess or quantitatively compare sites for development; (4) equip developers and producers to identify operational parameters in which the equipment and vessels will need to operate; (5) provide insurers and investors with the terminology to consistently assess risk and premiums; and (6) circumvent the emergence of narratives that root in different cognitive interpretations of the terminology in public discourse. This paper describes the evolution of the use of the term “offshore aquaculture” and define the most relevant parameters to shift to a more definitive and robust term “exposed aquaculture” that can inherently relay clearer information. Adoption of this more definitive definition of “exposed” will allow the user to define a site with more than just distance from shore. Key differences and the importance of these terms are discussed that affect various interest groups. Follow-up articles in this compilation from scientific members of the WGOOA as well as other scientists outside ICES are incorporated that develop a set of definitions and a rigorous exposure index.